2017
DOI: 10.1007/s00259-017-3865-3
|View full text |Cite
|
Sign up to set email alerts
|

Tumour functional sphericity from PET images: prognostic value in NSCLC and impact of delineation method

Abstract: Tumour functional sphericity was found to be dependent on the segmentation method, although the accuracy in retrieving the true sphericity was not dependent on tumour volume. In addition, even accurate segmentation can lead to an inaccurate sphericity value, and vice versa. Sphericity had similar or lower prognostic value than volume alone in the patients with lung cancer, except when determined using the FLAB method for which there was a small improvement in stratification when the parameters were combined.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(26 citation statements)
references
References 29 publications
1
25
0
Order By: Relevance
“…A and B for visual examples of the MATVs obtained using the two different segmentation approaches). The volume underestimation observed with the use of the 41% fixed threshold is in agreement with previous published studies [29][30][31][32] . This is most likely due to the highly irregular shapes in combination with the heterogeneous nature of uptake for the considered tumors.…”
Section: Radiomics Analysissupporting
confidence: 92%
“…A and B for visual examples of the MATVs obtained using the two different segmentation approaches). The volume underestimation observed with the use of the 41% fixed threshold is in agreement with previous published studies [29][30][31][32] . This is most likely due to the highly irregular shapes in combination with the heterogeneous nature of uptake for the considered tumors.…”
Section: Radiomics Analysissupporting
confidence: 92%
“…In [53], tumor heterogeneity evaluated by texture features at CT was a significant predictor of overall survival (OS) in NSCLC, but radiotracer uptake was not. CT-and PET-derived heterogeneity were both significant predictors of OS in [73], while Hatt et al [28] found an association between OS and PET sphericity, although their results also showed dependency on lesion volume and method used for segmentation. Positive association with different survival metrics and PET/CT texture features [37,54,73,74] or CT features alone [32,36,53] were also reported in other studies.…”
Section: Prediction Of Survivalmentioning
confidence: 87%
“…In most cases, their objective is to differentiate between round, smooth, and regular lesions from spiculated, elongated, and irregular ones. Apart from volume, common shape features are compactness, elongation, rectangular fit, spherical disproportion, sphericity, surface area, and surface-to-volume ratio [24,28,29]. Clearly, shape features are more easily assessed at CT than PET due to the higher image resolution of the former.…”
Section: Shape Featuresmentioning
confidence: 99%
“…Results using percentage thresholds have also been reported: for example, outlining 41% (49)(50)(51) or 25% of the SUV max in individual lesions and then summing them to calculate MTV (14,15). More complex image-processing methods, including gradient thresholds based on changes in the intensity of uptake at the edges of lesions (52); sourceto-background-corrected contours (53); and statistical methods such as clustering (54), fuzzy locally adaptive Bayesian (55), and others, have been proposed but not applied much in lymphoma and possibly have no clinical advantage over simpler methods (56).…”
Section: Which Thresholds Should Be Applied To Segment Mtv?mentioning
confidence: 99%